Pengaruh metode PQRST berbantuan media puzzle kalimat terhadap keterampilan membaca pemahaman - Dwi Tunggal Arina; Tawil Tawil; Putri Meinita Triana (Borobudur Educational Review, 2021)
This research aims to determine the effect of the PQRST method assisted by Sentence Puzzle Media on Reading Comprehension Skills for Grade 4 Students at SDN Banyakan, Mertoyudan District, Magelang District.The research design design uses a Pre-Experimental with the type of One Group Pretest-Posttest Design. Samples taken as many as 25 students through saturated sampling technique. The data collection method used in this research is the performance test. The validity test of intrumen by expert and using with SPSS 24.0 for windows like that reliability test. Prerequisite analysis test consist end from normality test, while data analysis used parametric statistical techniques, namely the Paired Sample T-test with the help of SPSS 24.0 for windows.The results showed the reading comprehension skills of the fourth grade students of SDN Banyakan before using the PQRST method assisted by sentence puzzle media (Pre test), the highest reading comprehension skills were 66, while the lowest was 13 with the average student being 41.20. The results of reading comprehension skills after using the PQRST method with sentence puzzle media (Post test) obtained the highest score of 87, the lowest score of 40 with the average reading comprehension skills of students was 62.76. Based on the results of the study showed that the PQRST method assisted by sentence puzzle media had a significant effect on reading comprehension skills of fourth grade students of SDN Banyakan. This is indicated by the tcount value of 16.800 with a sig = 0.00 (p <0.05).